(x-3)*6+1=65

Simple and best practice solution for (x-3)*6+1=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)*6+1=65 equation:


Simplifying
(x + -3) * 6 + 1 = 65

Reorder the terms:
(-3 + x) * 6 + 1 = 65

Reorder the terms for easier multiplication:
6(-3 + x) + 1 = 65
(-3 * 6 + x * 6) + 1 = 65
(-18 + 6x) + 1 = 65

Reorder the terms:
-18 + 1 + 6x = 65

Combine like terms: -18 + 1 = -17
-17 + 6x = 65

Solving
-17 + 6x = 65

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 17 + 6x = 65 + 17

Combine like terms: -17 + 17 = 0
0 + 6x = 65 + 17
6x = 65 + 17

Combine like terms: 65 + 17 = 82
6x = 82

Divide each side by '6'.
x = 13.66666667

Simplifying
x = 13.66666667

See similar equations:

| 2(x+3)/3+7/3=5(x-12)-2/3 | | 6(j-4)+j=-8 | | -10n+24+24n=-6n+24 | | 4x-8-3x=6x-2 | | -7x^2-5x+8=0 | | .44x+.25=.55x-.50 | | 18.42x-12.75=(5.32x-6.91)3.46 | | 1x+4=-8 | | 2-5x=-18 | | m^2-3m=10 | | 4x-2-3= | | 39+3x-12= | | 5y-3(2y-4)=8 | | c=5p+215 | | -19(z+2)+6(4z-4)=4(z-4)+11 | | -25=-5 | | (x-3).6+1=65 | | 2x^2-8x-5=0 | | 5y=10x+25 | | 10(5x+2)-3x=349 | | 16-3x=-4(4x+3)-4(-5-3x) | | 7x+9=19+5x | | -6x-5x=-2 | | n^2+5n-1=0 | | 2x-8=-7x+28 | | 7z=8z | | x-4=-1+8 | | 2x+4=5-6x | | 16-3x=-4(4x+3) | | 4(x-8)/5=16 | | 2y+(6+y)=12 | | x-8=6x-13 |

Equations solver categories